2013
DOI: 10.1002/jso.23376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation for lower abdominal aorta balloon occluding in the pelvic and sacral tumor resection

Abstract: The application of lower abdominal aorta balloon occluding to control hemorrhage during the surgery contributes to a more clear operation field, less operation time as well as less blood loss and blood transfusion. Moderate prolong of the occluding duration can improve the safety of the surgery and contribute to more radical resection of the tumor without increase of the risks for complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 17 publications
4
41
0
2
Order By: Relevance
“…Our study and some others (7,9,12,15,16,18) did not observe any vascular complications (except one patient in our study experienced occurred groin subcutaneous hematoma for incorrect compression of the puncture site). Typically, the longer the occlusion, the more complications.…”
Section: Follow-up Assessmentssupporting
confidence: 56%
See 2 more Smart Citations
“…Our study and some others (7,9,12,15,16,18) did not observe any vascular complications (except one patient in our study experienced occurred groin subcutaneous hematoma for incorrect compression of the puncture site). Typically, the longer the occlusion, the more complications.…”
Section: Follow-up Assessmentssupporting
confidence: 56%
“…Recently, several papers (7,9,12,15,16,18) claimed that occlusions of the lower abdominal aorta can effectively control intraoperative hemorrhage. Mi et al (9) reported that occluding the abdominal aorta with a balloon-dilation catheter effectively reduced intraoperative hemorrhage (blood loss volume was only 100-200 ml) and therefore assisted surgeons in the complete and safe resection of upper sacral tumors.…”
Section: Follow-up Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruptures of the occlusion balloon have occasionally been reported as complications of EBO, which can be avoided by monitoring the inflation pressure [6]. There are also reports of the use of REBOA in the setting of postpartum hemorrhage [7], pelvic surgery [8], and hepatobiliary surgery [9]. The use of REBOA in the setting of hemorrhagic shock in trauma population was first reported in 1954 during the Korean War [10], but it has been ignored for a long time due to lack of supportive data, lack of familiarity with the technique, the potential for visceral ischemia with irreversible damage, and the high complication rate (35%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there are 9 articles discussing the application of IABO on pelvic and/or sacrum tumors (8-16). 7 articles are case series or singlearm retrospective analysis with 30 cases or less (8-10, 12, 14-16), and 2 articles are retrospective studies with IABO group and non-IABO group (11)(12)(13). All of these authors believed IABO was associated with less intraoperative blood loss and different authors focused on different aspects, such as hemodynamic changes, postoperative complications or the prognosis of the tumor.…”
Section: Discussionmentioning
confidence: 99%